Factors Affecting the Preferences of Housing in Gated and Guarded Communities in Negeri Sembilan - Kayode Fadahunsi, Emmanuel; Cynthia Ohajion, Uchechi; Mathews, Soney (International Journal of Psychosocial Rehabilitation, 2020)
Gated communities are growing rapidly, contributing to spatial transformation in a very significant way. This in turn, has a great influence on urban development and social integration at the local level. It is obvious that a lot more of this type of housing are being developed across the country and they seem to become almost a dominant feature of Malaysian housing development projects. Developers see gated and guarded projects as an important niche marketing strategy in a competitive environment. As the customers’ preference on housing changes from time to time, analyzers will not be able to perform independent judgement and minimize the risks of uncertainty regarding residential housing preference without deep understanding of this behavior. There is urgency in studying these housing developments because they are growing uncontrollably. The preferences of residents’ need to be studied to know the differences in their choice, so it can be applicable for urban planning and housing provisions. This study therefore focuses on examining residents’ preferences for living in gated and guarded community in Negeri Sembilan, Malaysia. The study through data collected from 200 respondents examines influences like environmental factor, property physical factor, luxury and financial factor on the preferences of housing in gated and guarded communities. The data was analyzed in three ways: descriptive statistics were provided to determine the mean and standard deviation scores for the four factors; analysis of variance (ANOVA) tests was conducted to determine the relationship between the demographic profiles and respondents’ preferences; and SPSS analysis was employed to assess the hypothetical relationships between the factors and preferences of housing in gated and guarded communities. Results of the analysis revealed that the factors (property physical factor, luxury and financial factor) showed a positive influence on the preferences of housing in gated and guarded communities in Nilai, Negeri Sembilan while environmental factor has no relationship with the preferences of the respondents. Implications of these findings for researchers and estate developers were further discussed.